The cross-sectional determinants of inventory control and the subtle effects of ADRs - Hansch, Oliver (Journal of Banking & Finance, 2004)
This paper addresses the effects of international cross-listings on the domestic market by investigating the properties of market maker inventories on the London Stock Exchange. We find that the unit-root hypothesis can only be rejected for a fraction of dealer inventories, and that mean reversion is generally slow. Inter-stock variations in mean reversion can be explained by liquidity- and risk-related variables, as well as the availability of ADRs on other exchanges. We find that ADRs do have an appreciable and significant impact on dealer behaviour and trading costs. The findings have implications for our understanding of the subtleties of linkages between markets.